Addicted to rehab : race, gender, and drugs in the era of mass incarceration - McKim, Allison (Rutgers University Press, 2017)
Sociologist Allison McKim gives an in-depth and innovative ethnographic account of two women's rehab programs, one located in the criminal justice system and one located in the private healthcare system--two very different ways of defining and treating addiction. Her study ultimately reveals a two-tiered system, bifurcated by race and class. Â Â
Keywords: Drug addiction -- Treatment -- United States.; Drug addicts -- Rehabilitation -- United States.; Women's rights.; Substance-Related Disorders -- rehabilitation; Social Marginalization; Institutionalization; Women's Rights; Minority Health; Rehabilitation Centers -- ethics; United States; Toxicomanie -- Traitement -- États-Unis.; Toxicomanes -- Réadaptation -- États-Unis.; Femmes -- Droits.; POLITICAL SCIENCE -- Public Policy -- Social Security.; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare.; SOCIAL SCIENCE -- Social Classes.; Drug addiction -- Treatment; Drug addicts -- Rehabilitation; Drogentherapie; Haft; Weibliche Drogenabhängige; USA